Peran Organizational Learning Dan Intellectual Capital Dalam Menigkatkan Innovation Capability (Studi Pada Perusahaan Daerah Air Minum Tirta Mahakam Kabupaten Kutai Kartanegara) - Mawardi, Mawardi; Raharjo, Sugeng (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:This study examines aspects that contribute to the innovation capability of the Regional Water Supply Company Tirta Mahakam where the antecedent variable is human intellectual property originating from intellectual capital or intelligence capital with intervening organizational learning variables. The object of research in this study was the Regional Water Supply Company Tirta Mahakam Tenggarong. The analytical tool used is the method of structural equation modeling. The findings show that there is a significant influence of organizational learning on innovations capability. While the second finding shows that intellectual capital is not capable of influencing innovations capability.Â Keywords : Innovation capability, intellectual capital dan organizational learning